Environmental impact assessment of municipal solid waste management incorporating mechanical treatment of waste and incineration in Hangzhou, China. (10th January 2017) - Havukainen, Jouni; Zhan, Mingxiu; Dong, Jun; Liikanen, Miia; Deviatkin, Ivan; Li, Xiaodong; Horttanainen, Mika
Abstract: Municipal solid waste (MSW) management is becoming increasingly popular around the world as a means of accommodating the increasing amounts of waste that the growing global population generates. China currently produces more MSW than any other country. As such, this area of the world is facing challenges on an unprecedented scale. MSW management in China is highly dependent on landfilling, and the development of sanitary landfills is currently a top priority for the Chinese government. Hangzhou is one of the most developed cities in China. In fact, in 2013, the amount of incinerated MSW in Hangzhou represented 56% of total MSW. MSW incineration is primarily performed via a process of co-incineration with coal because MSW has a low heating value. This paper employs a environmental impact assessment by LCA program to determine whether refuse-derived fuel (RDF) production and incineration can have a more positive impact on the environment than the co-incineration of MSW with coal in Hangzhou, China. According to the results, RDF production and incineration could improve Hangzhou's MSW management global warming potential from −33% to 0%, the acidification potential from −90% to 34%, and the eutrophication potential from −1200%–350% in comparison to the co-incineration of MSW with coal. The treatment of organic reject material from RDF production has a significant effect on the results; as such, it should be utilized in energy production rather than landfilled. Highlights: Life cycle assessment of Chinese MSW management system was calculated. Impact of RDF incineration instead of MSW and coal co-incineration was studied. Importance of organic reject management from RDF production was highlighted.